CONDICIONANTES MORFOESTRUTURAIS E SUAS IMPLICAÇÕES NOS USOS DA TERRA E ÁREAS DE PRESERVAÇÃO PERMANENTE DA BACIA HIDROGRÁFICA DO SÃO JOÃO, CARAMBEÍ-PR - Pereira, Diely Cristina (2015)
Landscapes show standard which expose different intensity, duration and magnitude in long term physical-natural interaction and inter relational, in special in those referring to geological time. Any disturbance, internal or external, in its elements conducts to a reordering in its relations, resulting in new standard arrangements. This geological-geomorphologic natural disturbances are meaningful as they produce peculiar shapes and features, in different scale, which can add scenic value to the landscape as well as to devalue the soil fitness to agriculture. This way, the aim of this research was to analyze the landscape in São Jõao River Basin, from the linear structure in landforms and use of land. It has started by the hypotheses that linear structural feature presence acts as condition factor in the landscape in the referred basin, not only for limiting the use of land expansion but also for enlarging permanent preservation areas. The Basin is located in the Center- oriental mesoregion in Paraná, between the cities Castro e Carambeí, in the morphostructural transition between sedimentary Basin of Paraná and its basement, directly influenced by ascension movement of Ponta Grossa Arc. To reach to this objective, it was searched SRTM geomorphometric data , to map linear structural feature, which results in identification of 92 lineaments, like valleys/canyons, which average length is 1,33km, and predominant directions SE/NW, coincidently to the arc. Lineaments associate to the hydrographic system, in the special the ones from first and second order (Strahler, 1952), which valleys are embedded in steep slopes, usually bigger than 45o. Through morphometric analyses, using obtained data by Castro topographic map (SG-22-X-A-V-4), it has been detected that the Basin has irregular and elongated shape, and it houses a fluvial hydrographic system of 4 order, with low density of fluvial canals which shows lithostructural in drainage maintenance difficulty and big carving sheds. The field survey allowed to identify the predominance of litholic Neosol, intersected by rocky outcrop, which limit intense agriculture activities. Through supervised classification by LandSat 5 TM satellite image, on May 5th, 2011, it was identified as classes of land use: forest cover, forestry, fields and agricultural areas, and in lowest proportion, the urban area of Carambeí. In general, these uses have restriction in shallow soil properties. In strong slope, in permanent preservation area, all through the hydrographic system. The structural landscape in São João Basin ends a set of springs and enclosed valleys, which banks with minimum of 30m width, were defined as Permanent Preservation Areas, besides strands with superior 45o declivity. From the total area of São João River Basin, 15% is in this condition, fact that proves the initial hypothesis.